Tư liệu văn hiến Thăng Long - Hà Nội : Thần tích Hà Nội (Xếp theo ABC tên phường xã) / PGS.TS Nguyễn Thị Oanh (chủ biên); Dịch chú: TS. Đào Phương Chi, TS. Nguyễn Thị Hường, Th.s Nguyễn Thị Dương - Nguyễn Thị Oanh
Phụ lục: tr. 691-710